POLITICAL ISSUES IN RADIOHEAD'S SONG LYRICS(A CRITICAL DISCOURSE ANALYSIS ON THREE LYRICS IN RADIOHEAD'S ALBUM HAIL TO THE THIEF) - Daniel Cassa Augustinus, - (2008)
This study examines the issues of representation in three lyrics in the album of "Hail to the Thief" by Radiohead. In this study, the researcher employs van Dijk's model of Critical Discourse Analysis. Using this model, the three lyrics are analyzed from its macrostructure, superstructure, and microstructure then the result is discussed by framing in it in a wilder context and relating it intertextually to texts beyond the analyzed lyrics. The result of the investigation shows that the three lyrics represent political issues which are related to Radiohead views on war, election, and policies. The political issues are represented in implicit manner in the three lyrics. This is shown by the use of microstructure and superstructure elements in the three lyrics. The researcher also found that these issues implied an ideology which indicates an opposition toward capitalism.